Variables Linked to Academic Stress Related to the Psychological Well-Being of College Students Inside and Outside the Context of the COVID-19 Pandemic - Higinio Guillermo Wong Aitken; Helen Catalina Rabanal-León; Jesús Catherine Saldaña-Bocanegra; Nelly Roxana Carranza-Yuncor; Rafael Fernando Rondon-Eusebio (MDPI AG, 2024)
The present study examines the impact of academic stress on the psychological well-being of college students during and after the COVID-19 pandemic. The purpose of this study is to investigate similarities and differences in both scenarios. As a method, a review of the scientific literature was carried out following the PRISMA methodology. The Scopus and Web of Science databases were used by applying eligibility criteria and multiple filtering stages. Thirty-seven studies were selected for a qualitative content analysis. The results allowed for five groups of variables associated with academic stress to be categorized: (1) adaptation to change; (2) study modality; (3) learning resources; (4) academic-life balance; and (5) socio-emotional variables. The comparative analysis evidenced the exacerbation of academic stress and the comprehensive affectation of psychological well-being during the social restriction measures put in place due to the COVID-19 pandemic. In post-pandemic contexts, responses were mitigated by available social and affective resources. It was concluded that academic stress and its associated variables had more unfavorable consequences on the psychological well-being of college students due to social isolation measures with remote education during the pandemic.